Factors That Influence Adoption of Jajar Legowo Planting System in Sumber Makmur Farmer Group Kuwu Village, Balerejo, Madiun - Hamyana Hamyana; Diza Nurdiasari; Irianti Kurniasari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2020)
The background of this research is the low interest of farmers in the village of Kuwu to implement the jajar legowo planting system. Even though some studies show that the Jajar Legowo planting system has succeeded in increasing the productivity of rice plants. Based on these conditions, this study aimed to determine what factors influence the adoption of farmers in the application of the Legowo row planting system. The method used in describing the formulation of the problem in this study is a survey method with AMOS 22 Structural Equation Modeling (SEM) data analysis. The object of study is the legowo row farmers who are members of Sumber Makmur Village, Kuwu Village. The results of this study indicate that the adoption model of farmers is influenced by the attitudes and characteristics of innovation through the mediator variabel of perception and attitude. Hypothesis test results state that there is an influence of innovation characteristics on perceptions and attitudes towards adoption with a significance value of 0.001 which is smaller than 0.05.